Affectst of biotic and abiotic factors on some secondary metabolites in the root of Glycyrrhiza uralensis Fisch. - Gachmaa, Batzaya; Tsambaa, Battseren; Bayart, Mandakh; Indree, Tuvshintogtokh; Jukov, Azzaya (Mongolian Journal of Botany, 2024)
We aimed to examine the secondary metabolites in the root of G. uralensis from Eastern Mongolia and to see relationships between the content of these compounds depending on various factors such as region of plant growth, soil mechanic components, plant ontogenesis development stage, and whether it was cultivated or in the wild. G. uralensis root was collected from a total 9 soums of Dornod, Khentii, and Sukhbaatar provinces within 6 different ontogenesis stages. The contents of triterpene saponin (glycyrrhizin), and polysaccharide were determined by UV spectrometry using standard substances (Astragaloside IV, Glucose). The result of the research showed that the content of tritertenic saponins and polysaccharides in the root of G.uralensis were different depending on the stage of ontogenesis development as well as geographical location (p<0.05). On the other hand, we have found that the soil mechanic component doesn’t have an influence on these contents of G.uralensis root (p>0.05). One of the interesting results of the study is that the total saponin (glycyrrhizin) was different (p<0.05) within natural and cultivated samples, and the difference in the growing environment its statistically approved. In addition, when examining the relationship, it was found that triterpene saponin content of the G. uralensis root was negative related to the moisture content and positively related to the ash content (p<0.05), and the polysaccharide content was negative related to the ash content (p<0.05). These finding suggests that the concentration of these secondary metabolites in the root of G.uralensis can vary significantly depending on the ontogenesis development stage. Understanding how ontogenesis development influences the production of saponins and polysaccharides in this medicinal plant is crucial for optimizing its cultivation and harvesting practices for maximum yield and quality. Further research is needed to explore the specific mechanisms underlying this ontogenetic regulation of secondary metabolites in G. uralensis. Урал чихэр өвсний (Glycyrrhiza uralensis Fisch.) үндсэн дэх зарим хоёрдогч метаболитын агууламжид биотик болон абиотик хүчин зүйлсийн нөлөө Хураангуй. Бид Дорнод Монголын нутагт тархан ургаж буй Урал чихэр өвс (Glycyrrhiza uralensis Fisch.)-ний үндсэнд агуулагдах гол хоёрдогч метаболит (биологийн идэвхт нэгдэл)-ын агууламжид биотик хүчин зүйл (ургамлын онтогенез хөгжлийн үе шат), абиотик хүчин зүйлс (тухайн ургамлын ургаж буй газарзүйн байршил, хөрсний механик бүтэц, байгалийн болон таримал) хэрхэн нөлөөлж байгааг тодорхойлохын зэрэгцээ тухайн нэгдлүүдийн хоорондын хамаарлыг тогтоох зорилготой. Урал чихэр өвсний үндсийг Дорнод, Хэнтий, Сүхбаатар аймгийн нийт 9 цэгээс онтогенез хөгжлийн үе шатаар ялган авч, түүнд агуулагдах, тритерпент сапонин (глицирризин), полисахарын агууламжийг харьцуулан UV спектрометрийн аргаар стандарт бодис (Аstraglaside IV, Glucose)-ыг ашиглан тодорхойлсон ба чийг, үнслэгийг жингийн аргаар тогтоосон. Судалгааны үр дүнд онтогенез хөгжлийн үе шат буюу наснаас хамаарч Урал чихэр өвсний үндсэн дэх тритертент сапонин, полисахарын агууламж нь харилцан адилгүй ялгаатай байна (p<0.05). Газарзүйн байршил нь Урал чихэр өвсний үндсэнд агуулагдах тритертент сапонин (глицирризин), полисахарын агууламжид нөлөөлж (p<0.05) байгаа ба харин хөрсний механик бүтэц нь Урал чихэр өвсний үндсэн дэх тритертент сапонин, полисахарын агууламжид тодорхой нөлөө үзүүлэхгүй байгааг тогтоосон. Мөн нийлбэр сапонин (глицирризин) нь байгалийн ба таримал дээжид ялгаатай (p<0.05) буюу ба ургаж буй орчны хувьд ялгаа байгааг статистик судалгааны үр дүнгээр бататгав. Түүнчлэн хамаарлыг шалгахад Урал чихэр өвсний тритерпент сапонины агууламж нь чийгийн агууламжтай урвуу, үнслэгийн агууламжтай эерэг хамааралтай (p<0.05), полисахарын агууламж нь үнслэгийн агууламжтай урвуу хамааралтай байна (p<0.05). Урал чихэр өвсний үндсэд агуулагдах гол хоёрдогч метаболит болох нийлбэр сапонин, полисахарын агууламжид онтогенез хөгжлийн үе шат буюу нас абиотик хүчин зүйлс (тухайн ургамлын ургаж буй газарзүйн байршил, хөрсний механик бүтэц, байгалийн болон таримал)-ээс илүү нөлөө үзүүлдгийг бид тогтоолоо. Түлхүүр үгс: Нийлбэр сапонин, полисахар, хөрсний механик бүтэц, онтогенезийн үе шат